1984
DOI: 10.1007/bf01966785
|View full text |Cite
|
Sign up to set email alerts
|

The effects of antiallergic and bronchodilator drugs on platelet-activating factor (PAF-acether) induced bronchospasm and platelet aggregation

Abstract: Platelet activating factor (PAF-acether) is a potential mediator of asthma and inflammation. Recently, the suggestion was made that inhibition of PAF-acether by disodium cromoglycate (DSCG) might be partly responsible for the effectiveness of DSCG in asthma. We have extended these studies and examined the effects of antiallergic and bronchodilator drugs on PAF-acether induced bronchospasm after i.v. administration in guinea pigs and in vitro platelet aggregation in rabbits. Neither DSCG nor Wy-41,195, a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Disodium cromoglycate (DSCG) was completely inactive against the effects of Paf-acether in vitro, in accordance with in vivo results (Lewis et al, 1984), and in contrast to the inhibition described by Basran et al (1983) with very high concentrations applied with Pafacether to human skin. This indicates that the antiallergic activity of DSCG is not accounted for by inhibition of the effects of Paf-acether.…”
Section: Discussionsupporting
confidence: 87%
“…Disodium cromoglycate (DSCG) was completely inactive against the effects of Paf-acether in vitro, in accordance with in vivo results (Lewis et al, 1984), and in contrast to the inhibition described by Basran et al (1983) with very high concentrations applied with Pafacether to human skin. This indicates that the antiallergic activity of DSCG is not accounted for by inhibition of the effects of Paf-acether.…”
Section: Discussionsupporting
confidence: 87%
“…This may relate to the observation that while NDGA is a relatively selective inhibitor in vitro, its potency and effectiveness appear to be diminished in vivo [18]. The reasons for the disparity in the effects of aspirin, indomethacin, BW755C and NDGA on Paf-induced bronchoconstriction are not immediately obvious, but reflect the conflicting results of previous studies [19][20][21][22]. Both lipoxygenase and cyclooxygenase products have been implicated as mediators of Paf-induced bronchoconstriction.…”
Section: Discussionmentioning
confidence: 78%
“…Both lipoxygenase and cyclooxygenase products have been implicated as mediators of Paf-induced bronchoconstriction. LEWIS and co-workers [19] have reported that indomethacin at high doses, but not aspirin, attenuated and that BW 755C, NDGA and also the putative cysteinyl-containing leukotriene antagonist FPL 55712, at a high and probably non-selective dose, also reduced Paf-induced bronchoconstriction. In contrast, in separate studies FPL 55712, NDGA and eicosatetraynoic acid (ETYA), a false substrate inhibitor of the cyclooxygenase and lipoxygenase pathways, were reported not to influence bronchoconstriction induced by i.v.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, neither Wy-41,195 nor DSCG (both at 1-10 mg/kg, i.v.) influenced PAF-acether induced bronchospasm in anesthetized guinea pigs [16]. Furthermore, neither compound (at 10 .4 M) influenced PAF-acether induced rabbit platelet aggregation [16].…”
Section: Guinea Pig Skin and Airway Modelsmentioning
confidence: 97%